Peningkatan Hasil Belajar IPA Tema 3 Materi Benda dan Sifatnya Dengan Menggunakan Model Pembelajaran Cooperatif Tipe Talking Stick Pada Siswa Kelas III SD Negeri Wai Ina Kepualaun Sula - Harina Sangadji (Peneliti.net, 2022)
Active and interactive learning is what is to be achieved in the learning process, it is hoped that it will grow and develop the potential of students and optimize learning outcomes. One model that can be used in the learning process is the Talking Stick Type Cooperative learning model. This learning model places more emphasis on understanding the material taught by the teacher by answering questions so that students can be active in learning, so that their learning outcomes are maximized. The purpose of this study was to determine whether there was an increase in students' cognitive learning outcomes after using the Talking Stick Type Cooperative learning model. in the science subject, class III students at SD Negeri Wai Ina for the 2021/2022 academic year. This research is a class action research (CAR). The research was conducted in two cycles, the research subjects were class III students at SD Negeri Wai Ina consisting of 22 students. The material used by the researcher is an objective test of 10 questions at each meeting. Data collection techniques used are tests, observations, and documentation. The data analysis technique used is descriptive quantitative data analysis technique, namely by looking at the results of test data from a predetermined population. Based on the results of data analysis and discussion, it can be concluded that there is an increase in students' cognitive learning outcomes by applying the Talking Stick Type Cooperative learning model to the eyes. science lessons for class III students of SD Negeri Wai Ina. It can be seen from the 22 students who took 2 tests there was an increase in students' cognitive learning outcomes, the test in the first cycle some students were considered incomplete in terms of their learning outcomes, while in cycle II there was an increase which was considered successful with an average score above KKM 65.